1999
DOI: 10.1046/j.1365-2273.1999.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

A new acoustic method of differentiating palatal from non-palatal snoring

Abstract: Palatal snoring produces explosive peaks of sound at very low frequency (approximately 20 Hz). Using a digital sound trace a ratio of peak amplitude to root mean square amplitude can be calculated. This Peak Factor Ratio is significantly higher for palatal snores than non-palatal snores (P < 0.01). This acoustic method will be useful for selecting patients for palatal surgery as it is non-invasive and could be used in a home monitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 0 publications
4
37
0
1
Order By: Relevance
“…Osborne et al (1999) reported that explosive peaks of sound at very low frequency of approximately 20 Hz are produced in palatal snoring. This value is in a good agreement with the soft palate flutter frequency of 17.8 Hz predicted in our simulation.…”
Section: Discussionmentioning
confidence: 98%
“…Osborne et al (1999) reported that explosive peaks of sound at very low frequency of approximately 20 Hz are produced in palatal snoring. This value is in a good agreement with the soft palate flutter frequency of 17.8 Hz predicted in our simulation.…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, various publications differentiate specific snoring types and anatomic structures that may create specific snoring sounds. Tongue base snoring is reported to have predominant frequency patterns above 500 Hz and palatinal snoring below 500 Hz [3,4,1,2,[5][6][7][8]. Most data are based on the visualisation of vibrating structures during sleep endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst palatinal snoring is reported to have a main frequency below 500 Hz, the one found for tongue base snoring is above 500 Hz. Snoring episodes terminating obstructive apnoeas can exceed frequency maxima up to 4000 Hz [1][2][3][4][5][6][7][8]. Nevertheless, the data vary extremely depending on the method of recording and the parameters analysed.…”
Section: Introductionmentioning
confidence: 99%
“…Vibration of the soft palate is believed to generate a relatively low-frequency sound [19][20][21], and both surgical procedures reduced the energy content of the lowerfrequency sound bands with the most sustained effect being seen in the 0-250-Hz band. The transient change in periodicity observed in this study is also in keeping with a soft palatal effect, as studies in animals and humans [6] have shown that the flapping tremor of the soft palate produces a complex, lowfrequency (64-135 Hz), highly periodic waveform.…”
Section: Discussionmentioning
confidence: 99%
“…Snore periodicity is defined as the ratio of the number of periodic frames to the total number of frames. 4) Energy ratio: previous studies have characterised palatal snores as low-frequency sound [19][20][21]. Therefore, using a 1,024-point fast fourier transform (FFT), the energy content of the frequency sub-bands 0-200 Hz, 0-250 Hz and 0-400 Hz was calculated on a frame-by-frame basis at an update interval of 100 ms.…”
Section: Acoustic and Video Analysismentioning
confidence: 99%